Stakeholder arguments during the adoption of a sugar sweetened beverage tax in South Africa and their influence: a content analysis - Safura Abdool Karim; Petronell Kruger; Natasha Mazonde; Agnes Erzse; Susan Goldstein; Karen Hofman (Taylor & Francis Group, 2023)
Background Sugar-sweetened beverage (SSB) taxes are recognised as an effective intervention to prevent obesity. More countries are adopting SSB taxes, but the process of the adoption is politically complex. Objective This study aimed to analyse how public participation processes influenced the South African tax. Methods We conducted a content analysis of documents associated with the process of adopting the tax. Records were identified utilising the Parliamentary Monitoring Group database, including draft bills, meeting minutes and written submissions. The records were categorised and then inductively coded to identify themes and arguments. Results We identified six cross-cutting themes advanced by stakeholders: economic considerations, impact on the vulnerable, responsiveness of an SSB tax to the problem of obesity, appropriateness of an SSB tax in South Africa, procedural concerns, and structure of the tax. Stakeholder views and arguments about the tax diverged based on their vested interests. The primary policymaker was most responsive to arguments concerning the economic impact of a tax, procedural concerns and the structure of the tax, reducing the effective rate to address industry concerns. Conclusion Both supportive and opposing stakeholders influenced the tax. Economic arguments had a significant impact. Arguments in South Africa broadly echoed arguments advanced in many other jurisdictions.